Doctor's perspectives and practices regarding epilepsy - MARLEIDE DA MOTA GOMES (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The main aim of this study was to evaluate the knowledge, management practices and attitudes towards people with epilepsy (PWE) by a group of general practitioners (GP) and pediatrician (PD) residents. METHODS: A cross-sectional study was carried out in three training hospitals, and had been selected 31 GP and 47 PD who agreed with the study. The collection of data was made by self-applied structured questionnaire. RESULTS: Many respondents have positive values about PWE, and recognize prejudice in the population against them. The residents recognize in themselves and in the colleagues lack of knowledge about PWE, and that Medical School do not give enough importance to the study of PWE. The reference of PWE to the neurologist is a common practice among the doctors. Half of them are favorable to the idea of assuming the patients clinical management after an initial clientele appraisal by the neurologist. CONCLUSIONS: The non-neurologist doctors do not feel comfortable in managing PWE due to barriers. Our doctors complain about the undergraduate medical training related to the epilepsy. Although, there is not a clear relationship between the undergraduate medical training, referral practices and satisfaction about the management of PWE. The patients care is influenced not only by knowledge, but also by doctors' attitudes. In this way, there are other barriers, perceived or not, to providing care to PWE by the generalists, and they need to be approached in the medical undergraduate curriculum and medical continuing education.